(untitled) (Al-Aasar, 2025)
Islam is a religion that brings a message of guidance, mercy, and justice for all of humanity. The Holy Qur’an describes the Prophet Muhammad ﷺ as a “Mercy to all the worlds” (Rahmatul-lil-’Alameen), which clearly indicates that his prophethood was not confined to any specific nation or religious group but was universal in nature.A study of the Prophet’s ﷺ life reveals that he demonstrated the highest standards of character, wisdom, tolerance, and justice in his interactions with non-Muslims. These dealings were grounded in the teachings of the Qur’an, which emphasize human dignity, peaceful coexistence, and a wise, compassionate approach to inviting others to the truth.The Qur’an, at various instances, outlines principles for interacting with non-Muslims principles that include gentleness, fairness, good conduct, and the safeguarding of the dignity of believers. Acting upon these principles, the Prophet ﷺ established relationships with people of different communities, ethnicities, and religious beliefs. Whether in day-to-day social and commercial interactions, in formal treaties and agreements, or in his approach to da’wah (inviting to Islam), the Prophet ﷺ presented a model of balanced, noble character, always in accordance with Qur’anic guidance.This research study aims to highlight the various aspects of the Prophet’s ﷺ interactions with non-Muslims in light of the Qur’anic teachings. The objective is to demonstrate that Islam is founded not only on good treatment of its followers but also on principles of justice, goodwill, and respect for others. In today’s complex global and local contexts, this study seeks to draw guidance from the Seerah (biography) of the Prophet ﷺ to promote interfaith harmony and universal human values